2021
DOI: 10.1101/2021.03.21.436344
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Polycomb repressive complex 2 coordinates with Sin3 histone deacetylase complex to epigenetically reprogram genome-wide expression ofeffectorsand regulate pathogenicity inMagnaporthe oryzae

Abstract: The strict suppression and reprogramming of gene expression are necessary at different development stages and/or in response to environment stimuli in eukaryotes. In Rice Magnaporthe oryzae pathosystem, effectors from pathogen are kept transcriptionally silenced in the vegetative growth stage and are highly expressed during invasive growth stage to adapt to the host environment. However, the mechanism of how such effectors are stably repressed in the vegetative stage and its roles during rice blast infection r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…newly, the functions of PRC2 in the bio-trophic growth of M. oryzae, have also been discovered. It was found that to involved in regulating genes essential for host invasion, particularly the effector proteins (Zhang-W et al, 2021, Wu-Z et al, 2021. However, the exact role of the PRC2 complex during interactions between fungi and plants remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…newly, the functions of PRC2 in the bio-trophic growth of M. oryzae, have also been discovered. It was found that to involved in regulating genes essential for host invasion, particularly the effector proteins (Zhang-W et al, 2021, Wu-Z et al, 2021. However, the exact role of the PRC2 complex during interactions between fungi and plants remains unclear.…”
Section: Discussionmentioning
confidence: 99%